Assessing risk factors associated with breakthrough early post-traumatic seizures in patients receiving phenytoin prophylaxis - Generoso, Eugene; Diep, Calvin; Hua, Carolyn; Rader, Elizabeth; Ran, Ran; Lee, Nathanael J.; Rivera-Lara, Lucia (Frontiers in Neurology, 2024)
Objective: Post traumatic seizure (PTS) is a well-known complication of traumatic brain injury (TBI). The objective of this study is to identify risk factors associated with breakthrough early PTS in TBI patients receiving phenytoin prophylaxis. Methods: This was a single centered retrospective study including adult patients admitted to the intensive care unit (ICU), had a TBI, and started on phenytoin for seizure prophylaxis within 24 hours of admission. The primary outcome was the incidence and factors associated with early PTS, defined as a confirmed seizure on a continuous electroencephalogram within 7 days of TBI. Secondary outcomes included the association between early posttraumatic seizures and ICU length of stay, hospital length of stay and in hospital mortality. Results: A total of 105 patients were included in the final analysis. Patients with early PTS were older (65 vs 48 years old, p=0.01), had a higher Marshall score (5 vs 2, p=0.01), were more likely to have a Marshall score > 2 (73% vs 37%, p=0.01) and had more neurosurgeries for hematoma evacuation (57% vs 19%, p=0.01). In patients with early PTS, 87.5% had a therapeutic level (>10 mcg/mL) at the time of seizure. Patients with early PTS had a longer ICU length of stay (14.7 days vs 5.9 days, p=0.04) and a greater proportion of hospital mortality (21% vs 2%, p=0.02). Conclusion: Patients with higher age, Marshall score, and neurosurgical procedures for hematoma evacuation had higher incidences of breakthrough early PTS despite the use of phenytoin prophylaxis.